Legal Narratives, Human Trafficking and Slavery in Australia - Burn, Jennifer (History compass, 2017)
In this paper, I will explore the Australian context of human trafficking and slavery by reviewing narratives drawn from two separate coronial inquiries into the deaths of two people who were never legally recognised as being trafficked into Australia. Puongtong Simaplee died in Villawood Detention Centre in Sydney on 26 September 2001, and Manjit Singh died on 26 August 2011 in the intensive care unit of a Sydney hospital from complications of surgery.